2020
DOI: 10.14309/ajg.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Severe Acute Pancreatitis With Cyclooxygenase-2 Inhibitors: A Randomized Controlled Clinical Trial

Abstract: OBJECTIVES: Severe acute pancreatitis (SAP) is still a big challenge. Accumulated data showed that overexpression of cyclooxygenase-2 (COX-2) in acute pancreatitis and experimental pancreatitis could be attenuated with COX-2 inhibitors. This study was aimed to evaluate whether the occurrence of SAP could be prevented by selective COX-2 inhibitors. METHODS: A total of 190 patients with predicted SAP were randomized into convention group or convention plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 45 publications
0
38
0
3
Order By: Relevance
“…Patients who received the investigational drug had significantly lower levels of IL-6, and the therapy was associated with an almost 50% reduction in the progression of patients to severe disease. (12) This suggests that although IL-6 is a general marker of inflammation in many different disease states, and while not pancreas-specific, suppressing IL-6 levels by targeting either IL-6 itself or the upstream inflammasome in AP may lead to improved outcomes. (13) The mechanism of IL-6 activation is multifold and leads to downstream upregulation of the neutrophil response.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received the investigational drug had significantly lower levels of IL-6, and the therapy was associated with an almost 50% reduction in the progression of patients to severe disease. (12) This suggests that although IL-6 is a general marker of inflammation in many different disease states, and while not pancreas-specific, suppressing IL-6 levels by targeting either IL-6 itself or the upstream inflammasome in AP may lead to improved outcomes. (13) The mechanism of IL-6 activation is multifold and leads to downstream upregulation of the neutrophil response.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a study showed that cyclooxygenase-2 (COX-2) inhibitors can prevent AP from becoming severe recently [ 37 ]. This is the first report to demonstrate the effect of COX-2 inhibitors on the treatment of AP in humans.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, an obvious pancreatic and peripancreatic necrotic region shown in CT image, combined with elevated WBC count and neutrophil percentage during his hospitalization jointly indicated necrotic tissues-induced SIRS. Meanwhile, a clinical trial points out that inhibiting the inflammatory cascade in predicted SAP is of cost-effectiveness to strikingly reduce concurrence and promote the prognosis of SAP [ 12 ].…”
Section: Discussionmentioning
confidence: 99%